Research on the Connection of Heterogeneous Non-Metallic Materials in the Manufacture of Rocket and Space Technology Structures - Tamara Manko; Krystyna Kozis (Challenges and Issues of Modern Science)
In order to choose a method of joining dissimilar non-metallic materials in the manufacture of compartments of rocket and space technology, it is of particular interest to study the adhesion strength using a whole range of materials. These are glues, binders and fabrics that would guarantee high adhesive strength in the structure.